Breathing actions in butterfly swimming - Rushall, B. S. (1996)
For swimmers wishing to swim faster in butterfly races, there are biomechanical and mechanical benefits from swimming with a bi-lateral breathing action as long as vertical movements of the head and torso are minimized. This can usually be achieved by coaching swimmers to breathe below the water-line. For swimmers who perform bi-lateral breathing in crawl stroke, the adoption of this technique in butterfly should not be difficult.